Three Novel Mutations in the PHEX Gene in Chinese Subjects with Hypophosphatemic Rickets Extends Genotypic Variability - Jap, Tjin-Shing; Chiu, Chih-Yang; Niu, Dau-Ming; Levine, Michael A. (Calcified tissue international, 2011)
Mutations in the phosphate-regulating endopeptidase homolog, X-linked, gene ( PHEX ), which encodes a zinc-dependent endopeptidase that is involved in bone mineralization and renal phosphate reabsorption, cause the most common form of hypophosphatemic rickets, X-linked hypophosphatemic rickets (XLH). The distribution of PHEX mutations is extensive, but few mutations have been identified in Chinese with XLH. We extracted genomic DNA and total RNA from leukocytes obtained from nine unrelated Chinese subjects (three males and six females, age range 11–36 years) who were living in Taiwan. The PHEX gene was amplified from DNA by PCR, and the amplicons were directly sequenced. Expression studies were performed by reverse-transcription PCR of leukocyte RNA. Serum levels of FGF23 were significantly greater in the patients than in normal subjects (mean 69.4 ± 18.8 vs. 27.2 ± 8.4 pg/mL, P < 0.005), and eight of the nine patients had elevated levels of FGF23. Germline mutations in the PHEX gene were identified in five of 9 patients, including novel c.1843 delA, donor splice site mutations c.663+2delT and c.1899+2T>A, and two previously reported missense mutations, p.C733Y and p.G579R. These data extend the spectrum of mutations in the PHEX gene in Han Chinese and confirm variability for XLH in Taiwan.